2023
DOI: 10.1093/eurjcn/zvad066
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of patient education for patients with atrial fibrillation: nationwide cross-sectional survey and one-year follow-up

Abstract: Background Clinical practice guidelines recommend patient education for patients with atrial fibrillation (AF) as a part of holistic care, however clinical guidelines lack detailed specification the content, structure, and delivery of AF education programmes. Aim To examine the implementation of education for patients with AF in Denmark in relation to coverage, organization and content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A recent survey of AF service at Danish hospitals reported that under-use of patient education was explained by a lack of nursing resources, uncertainty in relation to what and how to deliver education, and low management priority. 23 …”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of AF service at Danish hospitals reported that under-use of patient education was explained by a lack of nursing resources, uncertainty in relation to what and how to deliver education, and low management priority. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence underscores the potential benefits of lifestyle modifications in AF management, with a specific focus on autonomic nervous system modulation [52]. These modifications exhibit the capacity to influence arrhythmia development and AF therapy by impacting autonomic tone [53,54]. Feasibility trials have probed the effects of autonomic modulation therapy, aiming to enhance AF management [55].…”
Section: Lifestyle Modifications For Managing Atrial Fibrillationmentioning
confidence: 99%
“…This impact is particularly pronounced on heart rate and parasympathetic modulation [58,59]. Intriguingly, music intervention in tandem with lifestyle modifications has shown promise in promoting autonomic balance among individuals with prehypertension and hypertension [54]. The potential of lifestyle changes to improve cardiac autonomic health and mitigate transient increases in cardiac autonomic modulation is also suggested [59].…”
Section: Lifestyle Modifications For Managing Atrial Fibrillationmentioning
confidence: 99%
See 2 more Smart Citations